The Effect of Traditional Fumigation on Physical, Mechanical and Anatomical Properties of Wooden Handicraft in West Kalimantan - Farah Diba; Lolyta Sisillia (Masyarakat Peneliti Kayu Indonesia, 2019)
West Kalimantan wooden craft is internationally well known and its export is increasing. Currently, high durability and attractive color of wood material such as belian (Eusideroxylon zwageri Teysm & Binnend) is rarely available, then alternatively mangium (Acacia mangium Willd.) and laban wood (Vitex pubescens Vahl.) are used for handicraft. Fumigation is one possible way to improve wood service life and color shades. This paper determines the impact of traditional fumigation on wood raw material on physical, mechanical and anatomical properties. The timber fumigation technique was conducted for one week, with curing time from early morning until late afternoon. After treatment, the physical, mechanical and anatomical properties of wood were evaluated. The different of color before and after treatment was measured by image processing scanner Canon P 145. Physical and mechanical properties refer to the British standard method. Result shows that fumigation improves the quality of wood, especially on color of wood. The wood became dark and more shining. It’s good for the handicraft materials. The quality of wood on moisture content value, both on mangium and laban wood was increased with average 30-50%. The average value of wood density of mangium wood after treatment with fumigation was 0.52, meanwhile laban wood was 0.55. The average value of radial shrinkage of mangium wood after fumigation treatment was 3.96% and tangential shrinkage was 6.34%. The average value of radial shrinkage of laban wood after fumigation was 6.43% and tangential shrinkage was 6.08%. The average value of hardness of mangium wood after fumigation treatment was 470.13 kg/cm2 and laban wood was 625.46 kg/cm2. The Fumigated wood color was darker and more attractive for decorative and craft products than non-fumigated wood. In general, this method could be used to preserve wood and to increase the physical performance of wood as raw material for handicraft.